2016
DOI: 10.1051/matecconf/20164701015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lime Addition on the Setting Time and Strength of Ambient Cured Fly Ash Based Geopolymer Binder

Abstract: Abstract.One of the limitations of geopolymer as the alternative binders in concrete is the necessity of heat curing. This study aimed to produce fly ash geopolymer binder subjected to ambient curing by adding a small proportion of lime and varying the activator dosage. The Class F fly ash from Mpanau coal-fired power plant was mixed with alkaline solution consists of sodium silicate and sodium hydroxide with Na2O dosage of 5%, 7%, and 9%. To achieve ambient cured paste, 8%, 9%, and 10% slaked lime was added a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…To achieve these purposes, some researchers have been focusing on the use of other alumino-silicates, like class C fly ash and GGBS [4][5][6]. Other researchers prefer calcium sources addition [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these purposes, some researchers have been focusing on the use of other alumino-silicates, like class C fly ash and GGBS [4][5][6]. Other researchers prefer calcium sources addition [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Using lime in alkaline activation mixtures has been explored in many research works. In the majority of them, the use of lime is limited to quantities between 1 and 20%, but normally at <10% [15][16][17][18][19]. Chakraborty et al [15] used sewage sludge ash (SSA), quick lime and blast furnace slag (BFS) as precursors activated with NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers focused on the utilization of other alumino-silicate materials such as the class C fly ash and GGBS (Guo, Shi and Dick, 2010;Law et al, 2012;Wardhono, Law and Strano, 2015) . Adding a small amount of calcium to class F fly ash is another alternative to avoid heat curing (Dombrowski, Buchwald and Weil, 2007;Yip et al, 2008;Khater, 2011;Adam et al, 2016). In our previous research, the ambient cured class F fly ash geopolymer paste was achieved by adding 8%, 9%, and 10% slaked lime as the partial substitute for the fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the addition of lime increased strength but decreased the setting time. The setting time of the fly ash based geopolymer paste can be controlled by adding up to 10% of slaked lime (Adam et al, 2016). This paper aims to produce ambient-cured geopolymer concrete through the addition of calcium in the mixture.…”
Section: Introductionmentioning
confidence: 99%